Importance of Timing of Dark Acclimation for Estimating Light Inhibition of Leaf Respiratory CO 2 Efflux - Bruhn, Dan; Griffin, Kevin L.; Møller, Ian M. (Plant, cell and environment, 2025)
The degree of inhibition of leaf respiration by light is often studied, but the methods used and the results obtained are variable. We suggest that in the future daytime leaf respiration is measured 3 min after dark acclimation to avoid under‐estimating the degree of light inhibition of leaf respiration. This will most likely speed up future surveys and perhaps also result in less inter‐study variation in the calculated degree of light inhibition of leaf respiration.